HINDU UPASANA VIS-A-VIS CHRISTIAN MEDITATION - Swami Bhajanananda (Journal of Dharma, 1977)
Upasana in Hinduism is the objective method of meditation in which importance is given to various objects of meditation. Etymologically upasana means "sitting near" (upa=near, dsana =seat), that is, approaching an object mentally. The mind is focused on a mental image. The original purpose of such meditations was to train the mind for the practice of oic bara I, the direct subjective method of self-enquiry. Patanjali studied the epistemological and psychological aspects of objective concentration in greater detail than anybody has ever done, and codified his research into a science of concentration. His method is to take the aspirant step by step, first through some preliminary disciplines, and then through a series of objective meditations, until he finally realizes his own true Self. His ideas are now indissolubly connected with every type of sadhana in vogue in Hinduism.